2015
DOI: 10.1371/journal.pone.0126840
|View full text |Cite
|
Sign up to set email alerts
|

Adding Content to Contacts: Measurement of High Quality Contacts for Maternal and Newborn Health in Ethiopia, North East Nigeria, and Uttar Pradesh, India

Abstract: BackgroundFamilies in high mortality settings need regular contact with high quality services, but existing population-based measurements of contacts do not reflect quality. To address this, in 2012, we designed linked household and frontline worker surveys for Gombe State, Nigeria, Ethiopia, and Uttar Pradesh, India. Using reported frequency and content of contacts, we present a method for estimating the population level coverage of high quality contacts.Methods and FindingsLinked cluster-based household and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 23 publications
5
100
1
Order By: Relevance
“…This is not surprising, as contact with a health provider does not necessarily mean that the necessary interventions were delivered with quality. Other studies have also found large gaps between coverage of care-seeking and effective or quality-adjusted coverage: for example Marchant et al found in 3 settings that quality coverage of ANC was 82%-93% lower than overall ANC coverage, and quality coverage of delivery was 41%-53% lower than overall coverage of institutional delivery [7]. Leslie et al found that across 8 countries, effective coverage of ANC was 44% lower than ANC4, and effective coverage of sick child care 62% lower than care-seeking for sick children [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not surprising, as contact with a health provider does not necessarily mean that the necessary interventions were delivered with quality. Other studies have also found large gaps between coverage of care-seeking and effective or quality-adjusted coverage: for example Marchant et al found in 3 settings that quality coverage of ANC was 82%-93% lower than overall ANC coverage, and quality coverage of delivery was 41%-53% lower than overall coverage of institutional delivery [7]. Leslie et al found that across 8 countries, effective coverage of ANC was 44% lower than ANC4, and effective coverage of sick child care 62% lower than care-seeking for sick children [10].…”
Section: Discussionmentioning
confidence: 99%
“…Health workers providing ANC, delivery or postnatal care, or child health services were interviewed about their training and supervision. For health workers who said that they assisted with deliveries, a module provided by the Informed Decisions for Actions in Maternal and Newborn Health (IDEAS) project was administered to ask about the interventions provided during the last delivery they assisted within the 12 months before the survey [7]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial overestimates in the life-saving potential of crude coverage compared to effective coverage estimates of life-saving interventions for mothers and newborns have been shown previously, for example in data from Tanzania [12], from India, Ethiopia and Nigeria [13], as well as from DHS-based data from Rwanda, Uganda, Namibia, Kenya, Ethiopia, Ghana and Mozambique [14].…”
mentioning
confidence: 84%
“…Moving beyond crude coverage to focus on effective coverage, defined as "the fraction of potential health gain that is actually delivered to the population through the health system, given its capacity", shifts the focus to acknowledge the importance of use and quality of services, in addition to need [11]. This focus on effective coverage has highlighted the quality gap in facility-based care for mothers and newborns in a variety of low and middle country settings [12][13][14].…”
mentioning
confidence: 99%